Critical thinking and hypothetic-deductive scheme for studying the elements of quantum theory - Serhii Tereshchuk; Sergii Sharov; Andriy Tereshchuk; Vira Kolmakova; Tetiana Sharova (Institute of Advanced Engineering and Science, 2023)
The study provided research and experimental verification of the hypothetic-deductive scheme for teaching the theory of quantum physics to secondary school students. The study highlighted the technologies and didactic tools, which help to boost the effectiveness of teaching physics to students and develop their critical thinking. It was found that the hypothetic-deductive scheme is based on the concept of critical rationalism and it has such stages: problem-hypotheses-rational criticism-choice of hypothesis-rational criticism of the new theory-new problem. The study described the stages of its implementation for teaching students the basics of quantum physics. To prove the effectiveness of the suggested scheme, the study carried out a comparative experiment in which 479 students took part (there were 241 students in experimental classes and 238 students in control classes). The statistical procession and interpretation of the experiment results were carried out with Pearson’s Chi-squared test. After the experiment, the quality of learning achievements that corresponds to the sufficient and high levels is 62.87% in the experimental classes, whereas in the control classes this figure is 52.48%. In further prospect, researchers plan to check the effectiveness of the suggested scheme to study other theories, which are studied in secondary school.